(untitled) (Revista de Biología Marina y Oceanografía, 2018)
Bathybembix bairdii, the Baird’s top shell, is reported for the first time from off the Baja California Peninsula west coast and the southwestern coast of Mexico, at depths of 710-2,093 m. Environmental conditions measured near bottom were: 2.10 to 5.81 °C, 34.40 to 34.63 (salinity), and <0.12-0.90 ml L-1 O2. The species was found mostly in muddy sediments dominated by silt (56.5-87.0%) (Baja California) or in sediments with a significant proportion of sand (63.5 to 88.5%) (southwestern Mexico). Shell height varied from 10.0 to 53.7 mm, with high proportion of large specimens in shallower water off Baja California. Densities varied from 1.75 to 207.45 org. ha-1 off Baja California and from 5.25 to 50.72 org. ha-1 in southwestern Mexico. Estimated maximum biomass occurred off southwestern Mexico (2.2 kg ha-1). Relationship between height and total weight (shell plus soft part) and between height and soft part weight were both highly correlated (R2: 0.933 and 0.928, respectively). Soft part weight varied from 29 to 62% of total weight and proportion increased with size. Mega invertebrate species associated with B. bairdii included 47% of decapod crustaceans, 35% of echinoderms, and 18% of mollusks. As a by-catch species regularly found in deep-water trawls, B. bairdii could represent a valuable resource for human consumption.